2011
DOI: 10.1039/c0jm03187a
|View full text |Cite
|
Sign up to set email alerts
|

A congruently melting and deep UV nonlinear optical material: Li3Cs2B5O10

Abstract: Single crystals of Li 3 Cs 2 B 5 O 10 have been synthesized and its structure determined by single-crystal X-ray diffraction. Li 3 Cs 2 B 5 O 10 crystallizes in the non-centrosymmetric space group C222 1 (No. 20). The structure consists of isolated B 5 O 10 groups that are bridged by LiO n (n ¼ 4, 5) and CsO n (n ¼ 8, 10) polyhedra through their vertex oxygen atoms to form an infinite three-dimensional structure. Li 3 Cs 2 B 5 O 10 melts congruently and exhibits a short-wavelength absorption onset at 175 nm. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(42 citation statements)
references
References 64 publications
4
36
0
2
Order By: Relevance
“…The formation of the new compound Ca 3 -(O 3 C 3 N 3 ) 2 (CCY), which occurs by the cyclotrimerization of cyanate ions, was examined thermoanalytically and the crystal structure was determined by single-crystal structure analysis. [3] Amongst these are Li 3 Cs 2 B 5 O 10 , [4] Li 6 CuB 4 O 10 , [5] and a high-pressure modifica-tion of BiB 3 O 6 . Second harmonic generation (SHG) measurements on crystal powders show a higher SHG efficiency for CCY than for BBO by about one order of magnitude.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of the new compound Ca 3 -(O 3 C 3 N 3 ) 2 (CCY), which occurs by the cyclotrimerization of cyanate ions, was examined thermoanalytically and the crystal structure was determined by single-crystal structure analysis. [3] Amongst these are Li 3 Cs 2 B 5 O 10 , [4] Li 6 CuB 4 O 10 , [5] and a high-pressure modifica-tion of BiB 3 O 6 . Second harmonic generation (SHG) measurements on crystal powders show a higher SHG efficiency for CCY than for BBO by about one order of magnitude.…”
mentioning
confidence: 99%
“…[1] This observation possibly also results from the fact that borates crystallize particularly often in non-centrosymmetric structures. [3] Amongst these are Li 3 Cs 2 B 5 O 10 , [4] Li 6 CuB 4 O 10 , [5] and a high-pressure modifica-tion of BiB 3 O 6 . LiB 3 O 5 (LBO), b-BaB 2 O 4 (b-BBO), and BiB 3 O 6 (BIBO) are among the most prominent representatives.…”
mentioning
confidence: 99%
“…The Na, Rb, and [Na 0.67 Ca 0.33 ] atoms reside in these tunnels, respectively, where Na atoms are located in a seven-coordination environment with Na-O bond lengths ranging from 2.369(6) to 2.546(3) Å, Rb atoms are located in an eight-coordination environment with Rb-O bond lengths ranging from 2.900 (6) Crystals 2017, 7, 10 2 of 9 structural unit to explore UV NLO materials. Additionally, it is well-known that the alkali metal and alkaline earth metal are ideal compositions in UV NLO materials because there are no electron transitions in the alkali metal-oxygen bond or alkaline earth metal-oxygen bond in the UV region [27][28]. Therefore, we expect that combining the [CO3] 2-groups with the alkali metal and alkaline earth metal will construct new kinds of UV NLO materials.…”
Section: Crystal Structure Descriptionmentioning
confidence: 99%
“…Thus, the [CO 3 ] 2-ion was selected as a basic structural unit 2 of 9 to explore UV NLO materials. Additionally, it is well-known that the alkali metal and alkaline earth metal are ideal compositions in UV NLO materials because there are no electron transitions in the alkali metal-oxygen bond or alkaline earth metal-oxygen bond in the UV region [27,28]. Therefore, we expect that combining the [CO 3 ] 2-groups with the alkali metal and alkaline earth metal will construct new kinds of UV NLO materials.…”
Section: Introductionmentioning
confidence: 99%
“…BO 3 groups present in the sample were identified by Fourier transform infrared spectrum. UV-vis-IR transmittance spectrum of BaBiBO 4 showed that it has a wide transmittance range from 310 nm to 3000 nm.In recent years optical materials have received great attention due to their interesting properties for technical applications [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Especially, inorganic borates have long been a focus of research due to their interesting nonlinear optical, transparency to a wide range of wavelengths, high laser damage tolerance, piezoelectric, luminescent and other useful properties for technical applications.…”
mentioning
confidence: 99%